Studies of the Direct Leaching of Zinc Concentrates and the Recovery of Elemental Sulfur from the Leach Residue - KUZUNO, Eiichi; FUJITA, Toyohisa; SHIBAYAMA, Atsushi; MIYAZAKI, Toshio; KAGAYA, Sakiko; MASUDA, Hitoshi (RESOURCES PROCESSING, 2001)
Zinc concentrate is usually roasted as pretreatment in zinc hydrometallurgy and the produced SO2 is changed to sulfuric acid. However, recently in Japan the utilization of sulfuric acid has been limited and it is more costly to store. In this study, a zinc concentrate (sphalerite) was leached with ferric sulfate at about 373 K for 3 to 6 hours. Then, zinc was leached about 94% and after a solid-liquid separation, the leach residue containing solid elemental sulfur was obtained. After direct leaching, the leach residue was filtrated and the elemental sulfur rich solids were recovered as float product by sink-float separation followed by flotation. In the flotation, lignine sulfonic acid salt as dispersant and MIBC as frother were effective to float sulfur at pH4. The solid elemental sulfur of approximately 97% was recovered as float product by sink-float separation and flotation. The dried mixed float product by sink-float separation and flotation was heated at 413 K for 2 hours and about 87.7% of solid elemental sulfur produced by direct leaching was recovered as pure sulfur.